Synthesis of cellulose nanofiber from Nypa fruticans shell collected from Can Tho City, Viet Nam - Quang Quoc Viet Thieu; Huynh Vu Thanh Luong; Thi Cam Tuyen Le; Tuan Loi Nguyen; Thi Hoang Thy Tran; Tuyet Ngan Nguyen; Ho Thai Bao Duong (CTU Journal of Innovation and Sustainable Development)
In this study, cellulose nanofiber (CNF) was synthesized from Nypa fruticans shells as raw material in Can Tho City. CNF was successfully produced via several steps. Firstly, raw material was treated with a mixture of Peroxyformic acid solution, then with an alkaline solution and bleached. Finally, it was hydrolyzed with 5% oxalic acid combined with hydrothermal and used ultrasonic waves with a high number of 40 kHz. The obtained materials after each step were surveyed and evaluated through advanced analysis methods, such as Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and scanning electron microscopy. The results indicate that the CNF material had high purity, high crystallinity, and an average size of about 15.74 nm. The results of this study demonstrate the potential of Nypa fruticans shells as a low-cost and environmentally friendly raw material for CNF synthesis.